Dynamic reconfiguration of node location in wormhole networks - SANCHEZ, J. L; GARCIA, J. M (Journal of systems architecture, 2000)
Several techniques have been developed to increase the performance of parallel computers. Reconfigurable networks can be used as an alternative to increase the performance. Network reconfiguration can be carried out in different ways. Our research has focused on distributed memory systems with dynamic reconfiguration of node location. Briefly, this technique consists of positioning the processors in the network depending on the existing communication pattern among them, to suit the requirements of each computation. In this article, we present a dynamic reconfiguration technique for wormhole networks. We have used both a crossbar and a multistage interconnection network to implement a reconfigurable logical two-dimensional (2-D) torus topology. The reconfiguration mechanism is based on a distributed reconfiguration algorithm. The algorithm is based on a cost function that requires only local information. We discuss reconfiguration features and adjust the different parameters of the reconfiguration algorithm. We have also studied the deadlock problem in reconfigurable wormhole networks, and give details of our solution. Finally, we have evaluated the performance of this technique under several workloads.